2014
DOI: 10.1016/j.jprocont.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design of fractional order linear system with stochastic inputs/parametric uncertainties by hybrid spectral method

Abstract: a b s t r a c tThis paper reports the design of a fractional linear system under stochastic inputs/uncertainties. The design methods were based on the hybrid spectral method for expanding the system signals over orthogonal functions. The use of the hybrid spectral method led to algebraic relationships between the first and second order stochastic moments of the input and output of a system. The spectral method could obtain a highly accurate solution with less computational demand than the traditional Monte Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Fractional derivative (FD) is a novel branch of derivative calculus, which is widely applied in the control systems, signal smoothing, biological engineering, and image processing [36][37][38]. Since integer-order derivative models may insufficiently represent the fractional order-based systems, the FD can better represent such issues [39].…”
Section: Introductionmentioning
confidence: 99%
“…Fractional derivative (FD) is a novel branch of derivative calculus, which is widely applied in the control systems, signal smoothing, biological engineering, and image processing [36][37][38]. Since integer-order derivative models may insufficiently represent the fractional order-based systems, the FD can better represent such issues [39].…”
Section: Introductionmentioning
confidence: 99%
“…This closed loop OP can be used to obtain the first-and second-order moment of the random output from (24). The parameters of the PI D controller can be obtained by optimizing the cost function defined as [37] min , , , ,…”
Section: Optimal Pi D Controller Designmentioning
confidence: 99%
“…The set point ( ) is a random process with a unit mean and covariance function ( ) = 0.01 ( ). This input ( ) can be viewed as a combination of the deterministic set point and zero mean measurement noise [37]. The control objective is to track the deterministic unit step input.…”
Section: (C) Example 2(c)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that first-and second-order derivatives have greater discrepancy from the raw data and are prone to missing data that impacts model precision. Meanwhile, fractional-order derivative as the derived concept of integer-order derivative is widely applied in the control system, signal smoothening, biological engineering, and image processing [17][18][19][20][21]. Its wide applicability is due to the fact that integer-order derivative models lack the precision when presenting the fractional order-based systems in real life.…”
Section: Introductionmentioning
confidence: 99%